2008
DOI: 10.1007/s11005-008-0241-z
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Behavior of Beta-Integers

Abstract: Beta-integers ("β-integers") are those numbers which are the counterparts of integers when real numbers are expressed in an irrational base β > 1. In quasicrystalline studies, β-integers supersede the "crystallographic" ordinary integers. When the number β is a Parry number, the corresponding β-integers realize only a finite number of distances between consecutive elements and are in this sense the most comparable to ordinary integers. In this paper, we point out the similarity of β-integers and ordinary integ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…There are also other aspects of numeration in non-standard systems that deserve to be explored. Properties, known for Rényi numeration with positive base, likely to hold also for the case of negative base, are for example the description of the distribution of (−β)-integers, given for positive base in [2], or the connection of (−β)-numeration to substitution dynamical systems established for β-integers in [6]. Many such properties are studied in [13] for number systems with positive base which are generalizations of the Rényi numeration.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…There are also other aspects of numeration in non-standard systems that deserve to be explored. Properties, known for Rényi numeration with positive base, likely to hold also for the case of negative base, are for example the description of the distribution of (−β)-integers, given for positive base in [2], or the connection of (−β)-numeration to substitution dynamical systems established for β-integers in [6]. Many such properties are studied in [13] for number systems with positive base which are generalizations of the Rényi numeration.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…As it holds for coefficients of the continued fraction of β that a 2n−1 = 1 and a 2n = p − 1, it suffices to consider even n in (1). We obtain then finally…”
Section: Index Of U βmentioning
confidence: 89%
“…As we have already said, the reader may find the notions of the Rényi expansion of unity, βintegers, distances between neighbors in Z β etc. in our precedent Letter [1]. However, in order to follow the ideas in the sequel, it is sufficient to know that u β is the unique fixed point of a morphism canonically associated with parameters p, q characterizing non-simple quadratic Parry numbers β.…”
Section: Infinite Words Associated With β-Integersmentioning
confidence: 99%
“…We have thus proved existence of constants so that (5) is valid. Let now v (1) , v (2) be factors of the infinite word ψ(u) with |v (1)…”
Section: Balanced Infinite Wordsmentioning
confidence: 99%
“…A class of one-dimensional sets studied for the BDL property is the family of the sets Z β for β > 1, where Z β is formed by the so-called β -integers, as defined in [6]. In [2], Gazeau et al have shown that Z β is BDL if β is a Pisot number. (Recall that α is a Pisot number if it is an algebraic integer greater than 1 with all algebraic conjugates in the interior of the unit disc.…”
Section: Introductionmentioning
confidence: 99%